Panic Purchasing: Food Hoarding in a City under Lockdown during the COVID-19 Pandemic - Nhan Thi Thanh Nguyen; Cuong Quoc Nguyen; Phat Tan Khuu; Kha Dao Huy Nguyen (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
This research aimed to investigate the determinants of panic purchasing to hoard food in Ho Chi Minh City during the lockdown caused by the COVID-19 pandemic. Pragmatism and the deduction approach were used for the research. During the lockdown period in Ho Chi Minh City, the purposive sampling technique was the first method used to reach the population that needed to be measured. Then, simple sampling was the second technique to collect data in the city in July and August 2021. Data were collected from 584 participants—higher than the required minimum sample size—who fulfilled the essential criteria to be included in the sample’s population. Multi-quantitative methods, including descriptive statistics, reliability tests for items, exploratory factor analysis, and linear regression analysis, were used to analyze the data obtained. The main findings are that perceived scarcity, susceptibility, severity, cues to action, and self-efficacy impacted panic purchasing to hoard foods. The results of this study are compared to the literature review in order to discuss panic buying behaviour, and recommendations are offered to policymakers and researchers in the future.